Research on dynamic cracking properties of cracked rock mass under the effect of thermal treatment. (December 2022) - Jiang, Yuanfeng; Zhou, Lei; Zhu, Zheming; Ma, Leijun; Chen, Jianxing; Li, Yaojia
Highlights: The effect of high temperature of granite and green sandstone fracture surfaces under impact loads was studied. The variation of fracture strength of specimens after different thermal treatments under impact loads was measured. The evolution law of dynamic cracking properties of specimens after different thermal treatments was measured. Abstract: Deep fractured rock mass is more prone to failure with the coupling effect of suddenly dynamic disturbances loads (explosions, seismic waves, etc.) and high temperature environment conditions, these factors have a great effect on the dynamic stability of fractured rock mass. In the present study, some traditional cracked straight through Brazilian disc (CSTBD) specimens made of granite and sandstone were heated from 25 °C to 700 °C to obtain dynamic fracture properties of high temperature soft and hard rocks. A modified traditional split Hopkinson pressure bar (SHPB) was applied for dynamic fracture experiments under impact loads, high speed camera, digital image correlation (DIC) and fracture surface scanning technology were used to study the fracture morphology of the specimens, the dynamic damage mechanism of high temperature soft and hard rocks under impact loads was obtained. The test results indicate that high temperature can greatly affect the roughness of the fracture surfaces under impact loads during crack formation and propagation, and the fractal dimension increases with the increase of temperature. Observing the dynamic fracture strength and fracture toughness of the CSTBD specimens, it can be found that the strength of the granite decreases gradually with high temperature treatment, and the dynamic fracture strength of the green sandstone increases firstly and then gradually decreases. At 500 °C–600 °C, the dynamic fracture strength of the two types of rocks decreases rapidly. Dynamic critical crack tip opening displacement of the specimens with different thermal temperatures increases with temperature, but the fracture process was similar and the cracks would follow the loading direction.